The Role of Enthusiasm in Developing Self-Awareness and Academic Resilience in Learning Nahwu/Dawr al-Hamas fi Tanmiyat al-Waʿyu al-Dhati wa al-Murunah al-Akadimiyyah fī Taʿallum ʿIlm al-Nahw - Amalia, Dian Risky; Bahruddin, Uril; Chamidah, Dewi; Yasmar, Renti; Daroini, Slamet; Fatiha, Belgheddouche (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2026)
The study of Ilmu Nahwu plays a central role in mastering the Arabic language; however, it continues to face various challenges, particularly in terms of student engagement and deep conceptual understanding. This study aims to examine the synergy between perception, cognition, and action in learning Nahwu through a psychopedagogical approach and to explore its impact on students’ self-awareness and academic resilience. Employing a qualitative method with an exploratory case study design, data were collected from five students of the Arabic Language Education Program at Universitas Ma’arif Lampung through in-depth interviews, classroom observations, and document analysis. The research instruments were developed based on a psychopedagogical framework, and the data were analyzed using Braun and Clarke’s thematic analysis. The findings indicate that high enthusiasm in learning Nahwu significantly shapes students’ comprehension of grammatical rules, positive attitudes toward the subject, and active engagement in the learning process. This enthusiasm is manifested in three interrelated dimensions: perception, cognition, and action. The interaction among these dimensions fosters not only a critical understanding of Nahwu but also the development of independent learning habits. Theoretically, this study positions enthusiasm as a key psychopedagogical construct that bridges perception, cognition, and action in Nahwu learning. Practically, the findings highlight the importance of implementing interactive teaching strategies that cultivate enthusiasm to strengthen students’ self-awareness and academic resilience, thereby promoting a sustainable and reflective learning culture in Arabic grammar education.